LIMA CERAMICS IN THE UPPER BASIN VALLEY FROM CENTRAL COAST - Mac Kay Fulle, Martín (2012)
This paper presents Lima ceramics from the upper drainage of the rivers from the central coast. It also deals with the links which should have existed between different segments of the valleys and redefines the term “Nievería”.